Estudo da usinagem de canais em quartzo alfa utilizando equipamento com spindle reclinável e disco abrasivo - Parreira, Shalom Reges (2025)
The machining of hard and brittle materials, such as ceramics and crystalline materials like quartz, is widely used in the construction of piezoelectric sensors and microelectromechanical systems (MEMS). The need to machine these materials efficiently and economically has become critical as the demand for affordable piezoelectric devices has increased, intensifying research in the area. Therefore, this work evaluated the performance of an experimental equipment, called C3L, with a tilting spindle for machining channels with an abrasive disk in polycrystalline alumina with 99.8% purity and monocrystalline α-quartz (AT plane) with the objective of verifying the ability of the C3L equipment to achieve results comparable to the commercial machine DISCO HI TECH DAD 3350. The C3L machine has a table with movement in Cartesian coordinates X, Y and Z and a bearing-mounted tilting spindle, capable of operating between horizontal and vertical positions. For this work, the project and construction of a flange for fixing the abrasive disk were developed. The equipment used as a reference for machining validation was a DISCO DAD3350 cutting machine, operating with an aerostatic spindle. The methodology for verifying failures consisted of dimensional analysis of chipping by optical microscopy, following a protocol already established in the literature that presents the average dimension of the chips caused by abrasive cutting as machining quality. The first material machined was a block of polycrystalline alumina (Al2O3), with 99.8% purity, measuring 34 × 34 × 8.5 mm. The part was ground to eliminate imperfections and the tests were carried out using an abrasive cutting disk model THERMOCARBON 2.25M-10C-54R7-3, which has an external diameter of 57.15 mm, thickness of 0.254 ± 0.010 mm, grain size of approximately 54 µm, and cooling was performed with water, applied manually. For alumina, with the same parameters applied in the commercial machine, the C3L showed average chipping of 15.69 µm against 20.50 µm of the DAD3350, representing an improvement of 23.5% in surface quality. However, angular misalignment was found between the spindle and the table, around Z, resulting in channel width 1.5 to 2.3 times the nominal thickness of the disk (254 µm). After aligning the table with a dial indicator, tests were carried out with quartz, which evaluated rotations (5,000; 10,000 and 15,000 rpm), feeds (0.1; 1 and 5 mm/s) and depths (0.1 and 0.3 mm); the smallest average flaw size (6.45 µm) occurred with a feed of 0.1 mm/s, depth of 0.3 mm and 10,000 rpm, while the largest average flaw size was identified in the cut with a feed of 5 mm/s, depth of 0.1 mm and 10,000 rpm, resulting in an average flaw size of 20.89 µm. Analysis of the tool after cutting revealed an asymmetric wear pattern on the disk, evidencing the misalignment, around Y, in the positioning of the spindle. It is concluded that, despite the need to correct the misalignment and implement automated cooling to optimize the process, the results demonstrate the technical feasibility of the C3L machine for machining α-quartz, with performance comparable to commercial equipment.